The Influence of Artificial Intelligence on Scientific Writing in the Academic Writing: Benefits, Challenges, and Ethical Considerations - Irfun Irfun; Muhammad Nurjaya; Ismail Maswatu (CV. Edujavare Publishing, 2025)
The rapid development of Artificial Intelligence (AI) technology has begun to significantly impact academic writing practices and processes. AI tools have increased writing efficiency, improved quality, and boosted student confidence, but have also raised ethical concerns such as plagiarism and over-reliance. The purpose of this study is to explore the multifaceted impact of artificial intelligence (AI) on scientific writing in academic settings from 2020 to 2025. This research method uses a Systematic Literature Review approach with quantitative and qualitative data from recent research. This paper is analyzed thematically with the effects of AI on academic productivity, learner psychology, and pedagogy. The results of this study indicate that recent empirical studies highlight substantial benefits and important challenges associated with the integration of Artificial Intelligence (AI) tools in the context of academic writing. This study concludes that the urgency of responsible AI integration, supported by governance and educational frameworks to maintain academic integrity and maximize the benefits of AI.